A four-component reaction for the synthesis of dioxadiazaborocines - Flagstad, Thomas (2015)
A four-component reaction for the synthesis of heterocyclic boronates is reported. Readily available hydrazides, α-hydroxy aldehydes, and two orthogonally reactive boronic acids are combined in a single step to give structurally distinct bicyclic boronates, termed dioxadiazaborocines (DODA borocines). In this remarkable process, one boronic acid reacts as a carbon nucleophile and the other as a boron electrophile to provide enantio- and diastereomerically pure heterocyclic boronates with multiple stereocenters in high yields.